Yield response of selected irrigated rice varieties to varying N, P and K fertilizer regimes (International Journal of Agricultural Research, Innovation and Technology, 2018)
Rice production has been inconsistent in Mwea irrigation scheme due to poor crop management practices and reduced soil fertility. Proper rice nutrition conserves the environment, increases sustained crop production, farmer’s crop yield and profits. A field experiment was conducted at MIAD Center, in Kirinyaga County, during 2016-17 and 2017- 18 to determine the response of rice varieties to different N, P and K fertilizer treatments. The trial was conducted in randomized complete block design, with three replications of 13 N, P and K fertilizer regimes as the main plots treatments and varieties Basmati 370 and BW 196 as the sub-plot treatment. The N kg ha-1: P2O5 kg ha-1: K2O kg ha-1 fertilizer treatment ratios used were: 00:00:00, 60:40:40, 80:60:60, 100:80:80, 60:40:00, 80:60:00, 100:80:00, 60:00:40, 80:00:60, 100:00:80, 00:40:40, 00:60:60 and 00:80:80. Plant height, number of tillers hill-1, panicle length, and grain yield responded positively to fertilizer application, but 1000-grain weight did not. Variety BW 196 recording shorter plants and panicles, more tillers hill-1, higher grain weight and yield than variety Basmati 370. 00:40:40, 00:60:60, 00:80:80, 60:40:00 and the no-fertilizer control treatments recorded the least number of tillers hill-1. 60:40:40, 80:60:60, 100:80:80, fertilizer treatments had longer panicles than the no fertilizer control and 00:40:40. Except for 100:80:00 and 00:40:40, in the first season and 60:40:00, 80:60:00, 100:80:00 in the second season, all the fertilizer regimes increased grain yield relative to the control. The highest grain yield was realized in fertilizer regime 80:60:60, 100:80:80, 80:00:60 and 100:00:80. 80:00:60 is the recommended fertilizer regime.Int. J. Agril. Res. Innov. & Tech. 8 (2): 42-46, December, 2018